PERTANGGUNGJAWABAN PIDANA DALAM KELALAIAN PEMBORONG YANG MENGAKIBATKAN BANGUNAN RUNTUH (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The progress of a country is largely determined by its ability and success in implementing development. Development as a planned change process covers all aspects of community life. The effectiveness and success of development is mainly determined by two factors, namely human resources, namely (the people involved from planning to implementation) and financing. All behavior of a person in society must be based on the applicable law. As we know, law is a human work in the form of norms containing behavioral guidelines. It is a reflection of the human will about how society should be nurtured and where it should be directed. Regarding the matter of construction, it cannot be separated from the contractor or contractor, where the condition of national construction services sometimes does not reflect expectations in realizing a quality building capable of functioning as planned.This type of research can be classified in the type of Normative legal research, which reveals legislation relating to legal theories that are the object of research. The approach taken uses a qualitative analysis approach by looking for data both in books, journals and other scientific works related to this research. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the results of the research are First, Criminal Liability for the negligence of the contractor which resulted in the project building collapsing in the construction process, there are two things that allow the corporation to act as a criminal (pleger), namely: First, in a general non-criminal liability crime. In this connection, the material actors are the head of the corporation / contractor / contractor, namely those who have a position to determine policies in the corporation. Second, Criminal Liability to parties related to the collapsed project building in the process of construction, it can be seen that the actions taken by one of the perpetrators contributed to the occurrence of a criminal act which created responsibility for the other perpetrator.Keywords: Criminal Liability, Contractors, Corporations, Buildings.